Sustainability, technology and innovation 4.0 - Borowiecki, Ryszard; Stuss, Magdalena M. 1973-; Makieła, Zbigniew (Routledge studies in innovation, organizations and technology, 2022)
"Sustainability, Technology and Innovation 4.0 is a holistic perception and analysis of innovation at the level of public organizations, innovation in industry and innovation in HR. Its chapters collectively present a thesis that Innovation 4.0 signals a technological revolution that has the opportunity to prevent environmental degradation, and in particular to stop climate warming, the effects of which may disrupt the process of sustainable development. Uniquely, this edited book offers a comprehensive and multi-faceted examination of Innovation 4.0, fulfilling methodical, empirical and utilitarian goals. The methodological objective is to present tools that allow the identification, analysis and assessment of the relationship between Innovation 4.0 and inspiration that will carry society towards a new economic and social order. Its empirical aim is to enable the analysis and evaluation of the role of public organizations, innovation in industry and innovation in HR in the process of building sustainable development of the global environment. The book's utilitarian goal is a recommendation for global organizations of Innovation 4.0 as an instrument to stimulate innovative economy. This is a high-level research book aimed at postgraduates, MBA students, researchers and academics from business colleges and universities, and may also provide valuable strategic perspective for business executives"--